Efforts to Improve Learning Outcomes in Dribbling Football Games through Learning Variations with Audiovisual Media - Tarigan, Jeri Franda; Devi Catur Winata; Suhariani (Jurnal Mahasiswa Pendidikan Olahraga, 2020)
This study aims to determine the increase in learning outcomes of dribbling by using the application of learning variations in class VIII students of SMP Private Amal Luhur Medan in the academic year 2019/2020. When the research was conducted in August 2019. It is seen that the students' initial ability in performing dribbling techniques is still low. Of the 30 students, 10 (33%) did not complete learning, while 20 (66%) had completed learning. With the average value of student learning outcomes is 60.97. Whereas in cycle II it can be seen that the students' ability to test classical learning outcomes has increased. Of the 30 students there were 26 students (87%) who had achieved mastery learning, while 4 (13%) had not yet achieved mastery learning. With an average value of student learning outcomes is 80.16. Based on this, it can be concluded that learning through the application of learning variations can improve learning outcomes in dribbling in class VII students of SMP Swata Amal Luhur Medan in the 2019/2020 academic year.